Prevalence of Barrett Esophagus in Adolescents and Young Adults With Esophageal Atresia. Issue 6 (December 2016) - Schneider, Anne; Gottrand, Frédéric; Bellaiche, Marc; Becmeur, François; Lachaux, Alain; Bridoux-Henno, Laure; Michel, Jean-Luc; Faure, Christophe; Philippe, Paul; Vandenplas, Yvan; Dupont, Claire; Breton, Anne; et al.
Abstract : Objective: To study the prevalence of Barrett esophagus (BE) (gastric and/or intestinal metaplasia) in adolescents treated for esophageal atresia (EA). Summary of Background Data: EA patients are at high risk of BE. Methods: This multicenter prospective study included EA patients aged 15 to 19 years. All eligible patients were proposed an upper endoscopy with multistaged esophageal biopsies under general anesthesia. Histological suspicion of metaplasia was confirmed centrally. Results: One hundred twenty patients [mean age, 16.5 years (±1.4)] were included; 70% had been treated for gastroesophageal reflux disease (GERD) during infancy. At evaluation, 8% were undernourished, 41% had received antireflux surgery, and 41% presented with GERD symptoms, although only 28% were receiving medical treatment. Esophagitis was found at endoscopy in 34% and confirmed at histology in 67%. BE was suspected after endoscopy in 37% and was confirmed by histology for 43% of patients (50 gastric and 1 intestinal metaplasia). No endoscopic or histological anomalies were found at the anastomosis site. BE was not significantly related to clinical symptoms. In multivariate analysis, BE was associated with EA without fistula ( P = 0.03), previous multiple antireflux surgery ( P = 0.04), esophageal dilation ( P = 0.04), suspicion of BE at endoscopy ( P < 0.001), and histological esophagitis ( P = 0.02). Conclusions: Patients with EA are at high risk of persistent GERD and BE. The development of BE is related to GERD history. Long-term systematic follow-up of the esophageal mucosa including multistaged biopsies is required, even in asymptomatic patients. (NCT02495051).